2018
DOI: 10.3389/fpsyt.2018.00701
|View full text |Cite
|
Sign up to set email alerts
|

Substance Dependence Among Bipolar, Unipolar Depression and Psychotic Homeless: A Canadian National Study

Abstract: Introduction: Homeless individuals are often mischaracterized as members of a homogeneous population that suffers from a wide mental health and addiction issues, with little consideration of potentially important differences within or between samples. The aim of the present study was to investigate the comorbidy of alcohol and/or substance dependence (ASD) and major psychiatric diagnoses (bipolar disorder, unipolar depression, and psychotic disorder) in a large Canadian sample of homeless individuals, and to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…(Habánik, 2018;Nishio et al, 2017). Among other factors, mental disorders play an important role, including psychotic disorders (Caton et al, 1994) and bipolar disorders (Maremmani et al, 2018). Fifty percent of HP have been considered to have some Kind of mental disorder (Scott, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…(Habánik, 2018;Nishio et al, 2017). Among other factors, mental disorders play an important role, including psychotic disorders (Caton et al, 1994) and bipolar disorders (Maremmani et al, 2018). Fifty percent of HP have been considered to have some Kind of mental disorder (Scott, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature tells us about the prevalence rates of alcohol and/or drug use problems among these individuals [ 24 , 25 , 26 ], highlighting how these two disorders are highly debilitating and often comorbid conditions [ 27 , 28 , 29 , 30 ]. Epidemiological research suggests that rates of comorbid substance use disorders are higher in bipolar disorder than in any other psychiatric disorder [ 3 , 31 , 32 , 33 , 34 , 35 ]. The Epidemiologic Catchment Area study reported that over 60% of those with bipolar disorder had a comorbid substance use disorder, with 46% meeting criteria for alcohol use or dependence and 41% meeting criteria for drug use or dependence [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has limitations. The findings are based on a cross-sectional survey done in one city, and therefore, caution is needed when extrapolating these findings across different homeless populations or across different time points as they may not be generalizable [ 62 ]. Moreover, although several factors may have contributed to our results.…”
Section: Discussionmentioning
confidence: 99%